Market basket analysis for improving the effectiveness of marketing and sales using Apriori, FP Growth and Eclat Algorithm - Khan, Mohammod Akib; Solaiman, Kazi Mohammad; Pritom, Touhid Hossain (BRAC Univeristy, 2017)
Cataloged from PDF version of thesis report.